Catalysts for Gas Purification: Highly Stable and Active Solid‐Solution‐Alloy Three‐Way Catalyst by Utilizing Configurational‐Entropy Effect (Adv. Mater. 16/2021). Issue 16 (20th April 2021) - Kusada, Kohei; Wu, Dongshuang; Nanba, Yusuke; Koyama, Michihisa; Yamamoto, Tomokazu; Tran, Xuan Quy; Toriyama, Takaaki; Matsumura, Syo; Ito, Ayano; Sato, Katsutoshi; Nagaoka, Katsutoshi; Seo, Okkyun; et al.
Abstract : PdRuM ternary solid‐solution‐alloy nanoparticles exhibit highly durable and active catalytic performance for automotive emission gas purification, which will result in a significant reduction in catalyst cost compared to rhodium. The work presented by Kohei Kusada, Michihisa Koyama, Hiroshi Kitagawa, and co‐workers in article number 2005206 provides insights into the design of highly durable and efficient functional catalysts, guiding how to best take advantage of the configurational entropy in addition to the mixing enthalpy.